Protein and Amino Acid Profile of Meals in Habitual Diets of Young Indian Women - Aggarwal, Renuka; Bains, Kiran (International Journal of Bio-resource and Stress Management, 2023)
The study was carried out among thirty young adult women (21–30 years) residing in hostels of Punjab Agricultural University, Ludhiana, Punjab during January, 2020 to assess the quantity and quality of protein in hostel diets. The duplicate meals in the daily diet of thirty institutionalized 21–30 years old young adult women were collected for seven consecutive days and analyzed for protein and amino acid content. The diets served on different days of the week were low in protein and lysine in all the meals but had adequate amount of other Indispensable Amino Acids (IAA).The three meals (breakfast, lunch and dinner) had low in vitro protein digestibility varying from 69.18% to 81.84% and a low Protein Digestibility-Corrected Amino Acid Score (PDCAAS) of 0.39, 0.46 and 0.39. On comparing the protein quality of three major meals of the diet, we found that all meals had a lower protein and lysine content with adequate amount of other IAAs. The overall digestibility of three meals was 74.58% with a PDCAAS of 0.42. The results indicated that diets of the young women living in hostels was low in protein quantity and quality especially in terms of amino acid lysine which is required for healthy body composition with higher muscle content. The quality protein deficiency in youth can affect muscle mass which can adversely affect the health thereby, leading to a rise in different types of diseases at later age.